Pharmacological Evaluation of Prosopis cineraria (L.) Druce in Gastrointestinal, Respiratory, and Vascular Disorders. (5th December 2012) - Janbaz, Khalid Hussain; Haider, Sajjad; Imran, Imran; Zia-Ul-Haq, Muhammad; De Martino, Laura; De Feo, Vincenzo
Abstract : In this paper, a crude methanolic extract from the stem bark of Prosopis cineraria, a plant native of Pakistan, was tested for its possible presence of spasmolytic, bronchodilator, and vasodilator activities in an attempt to validate some of its folkloric uses. Moreover, attempts were made to provide plausible explanations of the observed biological activities. The extract caused relaxation of the spontaneous as well as K + (80 mM)-induced contractions at tissue bath concentrations of 3–10 mg/mL in isolated rabbit jejunum preparations, probably mediated through blockade of Ca +2 channels. This finding was further confirmed by the shifting of the Ca +2 concentration response curves to the rightward in a manner similar to verapamil used as a standard Ca +2 channel blocker. The extract also exhibited nonspecific relaxant effect on carbachol (1 μ M)- and K + (80 mM)-induced contractions in isolated rabbit tracheal preparations. The same effect was recorded for phenylephrine (11 μ M) and K + (80 mM)-induced contractions in isolated rabbit aortic preparations in a manner similar to verapamil. These observations confirm that observed bronchodilator and vasodilator activities were possibly mediated through blockade of Ca +2 channels. The above-mentioned observations validate the traditional use of the plant in the treatment of respiratory and gastrointestinal ailments.